Preliminary Study of Rare Earth Element and Yttrium (REY) Content of Coal In Sangatta Coalfield, East Kalimantan, Indonesia - Anggara, Ferian; T.B.M. Petrus, Himawan; Patria, Aulia Agus; Bangun, Aya Shika (Indonesian Journal on Geoscience, 2020)
DOI:10.17014/ijog.7.3.305-314Kutai Basin is known as one of the most prolific sedimentary coal basins in Indonesia. Coal-bearing sequence in Kutai Basin is mainly Miocene to Eocene in age in which the coal seams are mostly in Miocene strata. Researchers have found that REY concentration in some coals and coal ashes are equal to or higher than that of the conventional deposit, as such coal deposit has become an important source for REY. Moreover, REY recovery as by-product from coal deposits could alleviate the â€œdirtyâ€ into â€œcleanâ€ coal energy. Referring to this shifted paradigm, a study on REY in Indonesian coal has put interest not only for researchers, but also for all stakeholders in this country. In this particular study, Sangatta coalfield in East Kalimantan was chosen as the area to observe the REY concentration. This area has been set due to its interesting geological setting, especially Pinang Dome that might have coal deposit with enriched REY. For the analyzed samples, drill cores were collected and then observed closely using polished section, inductively coupled plasma atomic emission spectroscopy (ICP-AES), and inductively coupled plasma mass spectrometry (ICP-MS). Based on the collected data, the highest REY concentration in coal deposit is located in the nearest part of the Pinang Dome. The REY content in coal deposit is associated with hydrothermal fluids and sediment source. These data suggest that there is a significant effect on Pinang Dome in the REY content in the coal deposit.